Facile synthesis of hierarchical mesoporous beta-manganese dioxide nanoflowers with extremely high specific surface areas for high-performance electrochemical capacitors. (10th September 2018) - Li, Rong-Bing; Yu, Li-Li; Li, Shuang; Fan, Jun; Luo, Rong; Zhao, Jing-Tai
Abstract: Ultrathin nanorods self-assembled porous nanoflowers to form hierarchical mesoporous beta -manganese dioxide (β-MnO2 ) with extremely high specific surface areas of >400 m 2 g −1 are fabricated in high yield at room temperature in a simple 1, 2-butanediol/KMnO4 system. As supercapacitor electrodes, specific capacitances of as-prepared β-MnO2 nanoflowers can reach 500-430 F g −1 at a current density of 0.1 A g −1 in 0.5 M Na2 SO4 aqueous electrolytes. And greatly enhanced rate capability of 66.4% at 20 A g −1 with a good cycling stability of 95.5% (10 A g −1, after 5000 cycles) is obtained by reducing the particle size of β-MnO2 nanoflowers with well-defined morphologies, which can be achieved by regulating the molar ratios of the reactants. In view of its easy preparation, the as-prepared β-MnO2 is considered as a promising candidate for high-performance supercapacitor electrode material. Graphical abstract: Image 1 Highlights: Hierarchical mesoporous β-MnO2 nanoflowers are high yield prepared (>95%) at room-temperature in a template-free approach. The as-prepared β-MnO2 nanoflowers have extremely large specific surface areas (>400 m 2 g −1 ). Hierarchical mesoporous β-MnO2 nanoflowers exhibit superior capacitive performance.